Implementation of Digital Literacy toward Pandemic Situation - Puji Hariati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This paper aims to describe the level of students’ digital literacy in their study since pandemic situation. It is very important to know because it gives the answer of education’s challenging faced covid-19 situation for the students’ safe and comfortable. This research is survey research to describe the implementation of digital literacy through level of digital literacy as challenging pandemic situation. Data collection techniques using the instrument in the form of a questionnaire. The four concept was constructed referred to Bawden (2008) such as basic literacy skills (reading and writing), background information knowledge (intellectual level), skills in the field of ICT, and attitudes and perspectives. This needs to be known to identify how far digital literacy was important for the students in their studying since Covid- 19 situation.  This research involved 20 respondents who always use digital literacy in their study. The data was collected from the distribution of digital literacy questionnaire instruments for the  students, then the data was describing through percentage to know how the students’ level of digital legacy when there are teaching learning process. The findings indicate that respondents have a high level of digital literacy. In the aspect of basic digital literacy skills, all respondents were able to connect to the platform to take part in online learning, and were able to use worksheet technology to write assignment articles according to the provisions. In the aspect of background information knowledge, almost all respondents were able to find learning supplements in the form of reference articles and find their relevance based on the abstracts of the articles. In the main aspects of digital literacy, most respondents are able to cite the relevant sections to compile assignment articles, and are able to compare the contents of several reference articles. On the aspects of attitudes and perspectives of information users, all respondents are able to write citations and compile a bibliography for reference articles referred to.